Pembelajaran Kooperatif Tipe Team-Accelerated Instruction (TAI) Untuk Meningkatkan Kemampuan Penalaran dan Komunikasi Matematika Siswa SMP - Nurahman, Iman (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2011)
Abstract Reasoning ability and student mathematics communication of Junior High School is important problem in mathematics learning. The main purpose of this study was to determine mathematical reasoning and communication skills students learn in cooperative learning type of TAI compared with students who are learning with conventional learning. This research is a form of experimental studies pre-test and post-test control group design. Experiment class obtained cooperative learning of TAI type and control class obtained learning conventional. The data was collected using a test instrument of the mathematical reasoning and communication ability, attitude scales, interview guides, and observation sheet. Research subjects were junior high school students, with a subject sample of Grade 7 students were randomly selected. Data obtained from the test results both pre-test and post-test and questionnaire of students opinion, as well as interviews with students were analyzed by descriptive. The results obtained are: 1) mathematical reasoning abilities of students receiving TAI type of cooperative learning better than students who received conventional learning, 2) mathematical communication skills of students receiving TAI type of cooperative learning is no better than those obtaining conventional learning, 3) there significant relationship between reasoning and communication skills of students in the experimental class, 4) there is no relationship between reasoning and communication skills of students in control class; 5) there is no relationship between reasoning ability and students' attitudes; 6) there is no relationship between communication skills and attitudes students; 7) students and teachers responded positively to the TAI type of cooperative learning; and 8), cooperative learning activities of students during type TAI performing well and conducive. Key words: cooperative learning, team-Accelerated Instruction, mathematical reasoning ability, communication skills of math Abstrak Kemampuan penalaran dan komunikasi matematis siswa SMP adalah masalah yang penting dalam pembelajaran matematis. Tujuan utama penelitian ini adalah untuk mengetahui kemampuan penalaran dan komunikasi matematis siswa yang belajar dengan pembelajaran kooperatif tipe TAI dibandingkan dengan siswa yang belajar dengan pembelajaran konvensional. Penelitian ini merupakan studi eksperimen berbentuk pre-test dan post-test control group design. Kelas eksperimen memperoleh pembelajaran kooperatif tipe TAI dan kelas kontrol memperoleh pembelajaran konvensional. Pengumpulan data dilakukan dengan menggunakan instrumen berupa tes kemampuan penalaran dan komunikasi matematis, skala sikap, pedoman wawancara, dan lembar observasi. Subjek penelitian adalah siswa SMP, dengan subjek sampel siswa kelas 7 sebanyak dua kelas dari yang dipilih secara acak. Data yang diperoleh dari hasil tes baik pre-test maupun post-test, angket pandapat siswa dan hasil wawancara dengan siswa dianalisis secara deskriptif. Hasil yang diperoleh adalah: 1) kemampuan penalaran matematis siswa yang memperoleh pembelajaran kooperatif tipe TAI lebih baik daripada siswa yang memperoleh pembelajaran konvensional; 2) kemampuan komunikasi matematis siswa yang memperoleh pembelajaran kooperatif tipe TAI tidak lebih baik daripada yang memperoleh pembelajaran konvensional; 3) terdapat hubungan yang signifikan antara kemampuan penalaran dan komunikasi siswa di kelas eksperimen; 4) tidak terdapat hubungan antara kemampuan penalaran dan komunikasi siswa di kelas kontrol; 5) tidak terdapat hubungan antara kemampuan penalaran dan sikap siswa; 6) tidak terdapat hubungan antara kemampuan komunikasi dan sikap siswa; 7) siswa dan guru memberikan respon postitif terhadap pembelajaran kooperatif tipe TAI; dan 8) aktivitas siswa selama pembelajaran kooperatif tipe TAI terlaksana dengan baik dan kondusif. Kata kunci: pembelajaran kooperatif, Team-Accelerated Instruction, kemampuan penalaran matematis, kemampuan komunikasi matematis